Mediação docente diferenciada: uma investigação sobre autoconhecimento docente e pedagogia diferenciada a serviço da relação professor-aluno - Stein, George Ricardo (2022)
This research analyzes how the adoption of pedagogical practices based on differentiated instruction and teacher self-knowledge, through the use of the MBTI® (Myers and Briggs Type Indicator), influences the teacher-student relationship from the perspective of teachers. Additionally, it proposes initial elements for a differentiated teacher-student mediation outlining a theoretical construct. It adopts a theoretical framework that integrates the themes of differentiated instruction, mediation and self-knowledge by psychological types. This integration is articulated through teacher training references and curriculum theories. An action-research integrated with a continuing education program in didactic differentiation by psychological types was developed for twenty-six elementary school teachers in a private school in the state of São Paulo. During the training program, participants gradually applied theory in the classroom and collected information on the practices adopted. The information obtained was quantitatively and qualitatively evaluated in the action research cycle, so as to keep the training program and investigation in line with the previously defined objectives. The results indicate that self-aware teachers are able to identify and better deal with the diversity of behaviors of students in the classroom, thus assuming a pedagogical intention to plan teaching activities and interact with students, realizing positive aspects related to attention, participation and contribution of students in the classroom. The analyses brought contributions to future editions of continuing education programs, as well as the detailing of a theoretical construct of differentiated teacher-student mediation that would make it possible to extend the relevant aspects to other contexts